2001
DOI: 10.1038/sj.bjp.0703822
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the long‐acting tachykinin NK1 receptor antagonist MEN 11467 on tracheal mucus secretion in allergic ferrets

Abstract: We investigated the effect of MEN 11467 ((1R,2S)‐2‐N[1(H)indol‐3‐yl‐carbonyl]‐1‐N‐{Nα(p‐tolylacetyl)‐Nα(methyl)‐D‐3‐(2‐naphthyl)alanyl}diaminocyclohexane) on tachykinin‐induced mucus secretion in ferret trachea in vitro and determined its effect on secretion by tracheae from allergic ferrets in response to allergen challenge. Repeated administration of [Sar9,Met(O2)11]‐substance P ([Sar9]SP, 1 μM) maintained mucus output above control values for at least 1.75 h. MEN 11467 inhibited secretion in a concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Further evidence for this hypothesis is provided by their work demonstrating increased expression of substance P and its receptor in asthmatics, which was correlated with the mucus content in the airway epithelium. 43 In conclusion, the tachykinin NK 1 receptor is involved in the secretory response of goblet cells, [44][45][46][47][48] and we provide evidence for an involvement of this receptor in proliferation of these cells induced by antigen.…”
Section: Discussionmentioning
confidence: 95%
“…Further evidence for this hypothesis is provided by their work demonstrating increased expression of substance P and its receptor in asthmatics, which was correlated with the mucus content in the airway epithelium. 43 In conclusion, the tachykinin NK 1 receptor is involved in the secretory response of goblet cells, [44][45][46][47][48] and we provide evidence for an involvement of this receptor in proliferation of these cells induced by antigen.…”
Section: Discussionmentioning
confidence: 95%
“…We also showed by using the hillocks technique that SP is a potent airway submucosal gland secretagogue confirming reports using the same technique in pig (Haxhiu et al ., 1990) and other techniques in different species such as human (Rogers et al ., 1989), dog (Haxhiu et al ., 1988), ferret (Khan et al ., 2001), rat (Wagner et al ., 1999), and also in pig (Trout et al ., 2001) airways. The concentration of SP (1 μ M ) is commonly used in many studies of gland secretion (Rogers et al ., 1989; Haxhiu et al ., 1990; Wagner et al ., 1999; Trout et al ., 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been demonstrated that chronic inhalation of nicotine induces a shift from serous to mucous glands in the airways of ferrets [227]. More recently Khan et al, [228] has demonstrated that in the tracheae of ovalbumin sensitized animals repeated administration of ovalbumin continued to maintain mucus output above controls. In spite of these favorable features however the recent increase in the use of the ferret in asthma-related research resulted from another characteristic of this animal.…”
Section: Ferretmentioning
confidence: 98%